Competitive dynamics of peruvian grapes in the United States and the netherlands markets - Lazo Calanche, Meredyth Ernestina Leslye (2020)
The growth of Peruvian fresh grapes exports encouraged the study of its competitive dynamics in the period 2010-2017. The two main world importers of the product, i.e. the United States and Netherlands were analyzed. The Relative Trade Balance, Tradability indices with the sub-indicators: Export Openness Degree and Import Penetration Degree, Symmetric Comparative Advantage and the Market Insertion Matrix, interlacing Positioning and Efficiency, were estimated. The research found that Peru and South Africa were fresh grapes competitive producers in both markets among 12 evaluated countries.